2014
DOI: 10.1038/cdd.2014.183
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic BRAF induces chronic ER stress condition resulting in increased basal autophagy and apoptotic resistance of cutaneous melanoma

Abstract: The notorious unresponsiveness of metastatic cutaneous melanoma to current treatment strategies coupled with its increasing incidence constitutes a serious worldwide clinical problem. Moreover, despite recent advances in targeted therapies for patients with BRAF V600E mutant melanomas, acquired resistance remains a limiting factor and hence emphasises the acute need for comprehensive pre-clinical studies to increase the biological understanding of such tumours in order to develop novel effective and longlastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(131 citation statements)
references
References 53 publications
5
119
0
Order By: Relevance
“…Specifically, higher expression levels of all autophagy-related proteins were observed in PTCs with the BRAF V600E mutation, compared to those without the BRAF V600E mutation. In support of this finding, previous studies have observed an association between the BRAF V600E mutation and increased autophagy [23,24]. This association may be attributed to multiple factors.…”
Section: Discussionsupporting
confidence: 79%
“…Specifically, higher expression levels of all autophagy-related proteins were observed in PTCs with the BRAF V600E mutation, compared to those without the BRAF V600E mutation. In support of this finding, previous studies have observed an association between the BRAF V600E mutation and increased autophagy [23,24]. This association may be attributed to multiple factors.…”
Section: Discussionsupporting
confidence: 79%
“…Similarly, oncogenic transformation driven by loss of the tumor suppressors p53, PTEN, TSC1 or TSC2 dramatically enhances protein synthesis rates, leading to ER stress (Hart et al, 2012; Namba et al, 2015; Signer et al, 2014). Enhanced protein synthesis and concomitant ER stress are also observed upon overexpression of oncogenic HRAS (G12E), BRAF (V600E), c-Myc or Src (Chen et al, 2014; Corazzari et al, 2015; Denoyelle et al, 2006). Importantly, both the UPR signaling and leukemia development induced by conditional PTEN deletion (Signer et al, 2014) or c-Myc overexpression (Hart et al, 2012) were dramatically reduced or entirely abrogated upon heterozygous deletion of the key translation rate regulator ribosomal protein L24.…”
Section: Sources Of Er Stress In Tumorsmentioning
confidence: 99%
“…Conversely, oncogenic BRAF induces a chronic ER stress status, resulting in enhanced basal autophagy [as evidenced by increased Atg8-PE/LC3-II (LC3-II) expression], resistance of melanoma cells to apoptosis, and insensitivity to further autophagy induction. This suggests that although melanomas rely on increased innate autophagic activity, BRAF-mutated tumors are resistant to further mTOR-dependant stimulation of autophagy and that while combined inhibition of autophagy with chemotherapy might be a viable therapeutic avenue for BRAF wild-type melanomas, targeted therapies that attenuate ER stress may prove a more effective treatment strategy for BRAF mutant melanomas (12, 18, 19). …”
mentioning
confidence: 99%